2021
DOI: 10.1016/j.esxm.2021.100324
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a Patient Education Resource for Male Hypogonadism and Testosterone Therapy

Abstract: Introduction YouTube is an unregulated platform that patients are using to learn about treatment options. Aim To assess the reliability of YouTube videos (YTVs) related to male hypogonadism and testosterone therapy. Methods Searching on YouTube by relevance and view count, we analyzed the top 10 videos (80 videos total) for the following search terms: low testosterone, testosterone replacement therapy, AndroGel, and hypogonadism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 15 publications
1
1
0
3
Order By: Relevance
“…Similarly, non-physicians' videos are viewed more than physicians'. 14 In our study, we found a similar result that YTVs had lowquality information uploaded by non-physicians (p<0.000) and on the contrary, we didn't find a dif-ference in view counts between physician's and non-physician's videos that included transdermal testosterone usage (p=0.952).…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, non-physicians' videos are viewed more than physicians'. 14 In our study, we found a similar result that YTVs had lowquality information uploaded by non-physicians (p<0.000) and on the contrary, we didn't find a dif-ference in view counts between physician's and non-physician's videos that included transdermal testosterone usage (p=0.952).…”
Section: Discussionsupporting
confidence: 64%
“…Literatürde, farklı tanılara ait video analizlerinde, bu oran %30 ile %54 arasında değişmektedir. [24][25][26] Bunun sebebi analiz edilen hastalıkla ilgili olabilir. Çünkü şimdiye kadar yapılan video analizleri PMR'nin aksine görülme sıklığı ve toplum tarafından bilinirliği yüksek, eklem deformitesi gibi süreğen sorunlara yol açan hastalıklardır.…”
Section: Discussionunclassified
“…(2020; [ 95 ]) YouTube Qualitativ Laien + 1 70 Warren et al. (2021; [ 96 ]) YouTube Quantitativ manuell + Profis Laien + 1 Gering 71 Whiteley et al. (2020; [ 97 ]) YouTube Quantitativ manuell + Profis 1 72 Yeo und Chu (2017; [ 24 ]) Facebook Quantitativ manuell Laien 5 a Gliederung der Anbieter in 3 Gruppen: Profis (Fachleute für sexuelle Gesundheit, Organisationen der sexuellen Gesundheit), Laien (Laien/Peer Sex Educators), Sonstige (Medienorganisationen/Fachleute für Medien und Kommunikation, kommerzielle Anbieter, andere Anbieter) b Anzahl der behandelten Themenbereiche aus 6 Themenbereichen (1 HIV/STI, 2 geschlechtliche und sexuelle Identitäten, 3 sexuelle Gewalt, 4 Fruchtbarkeit und Verhütung, 5 sexuelle und reproduktive Störungen, 6 sexuelle Funktionen, Lebensstile und Vergnügen) c Klassifikation der Qualitätsausprägung als gering (51–100 % – also mehr als die Hälfte – der Untersuchungseinheiten mit Qualitätsmängeln), mittel (11–50 %), hoch (0–10 %; Tab.…”
Section: Methodeunclassified
“…(2017; [ 88 ]) N = 50 meistgesehene englischsprachige YouTube-Videos zum Hormonimplantat als Verhütungsmethode 24 % der Videos (12) von Gesundheitsprofis mit höherem DISCERN-Index (Md = 3) 76 % der Videos (38) von Patient:innen mit geringerem DISCERN-Index (Md = 2) Warren et al. (2021; [ 96 ]) N = 72 meistgesehene englischsprachige YouTube-Videos zu männlichem Hypogonadismus und Testosteronersatztherapie 38 % der Videos (27) von Gesundheitsprofis mit höherem DISCERN-Index (M = 3,22) 62 % der Videos (45) von Gesundheitslaien mit geringerem DISCERN-Index (M = 1,87) Whiteley et al. (2020; [ 97 ]) N = 58 englischsprachige YouTube-Videos zur HIV-Präexpositionsprophylaxe (HIV-PrEP) Keine Gesamtbewertung der Qualität der Informationen in der Stichprobe vorgenommen n = 10 Publikationen mit standardisierter Messung der Informationsqualität.…”
Section: Ergebnisseunclassified